Large‐amplitude electric fields in the inner magnetosphere: Van Allen Probes observations of subauroral polarization streams. Issue 6 (17th June 2016) - Califf, S.; Li, X.; Wolf, R. A.; Zhao, H.; Jaynes, A. N.; Wilder, F. D.; Malaspina, D. M.; Redmon, R.
Abstract: The subauroral polarization stream (SAPS) is an important magnetosphere‐ionosphere (MI) coupling phenomenon that impacts a range of particle populations in the inner magnetosphere. SAPS studies often emphasize ionospheric signatures of fast westward flows, but the equatorial magnetosphere is also affected through strong radial electric fields in the dusk sector. This study focuses on a period of steady southward interplanetary magnetic field (IMF) during the 29 June 2013 geomagnetic storm where the Van Allen Probes observe a region of intense electric fields near the plasmapause over multiple consecutive outbound duskside passes. We show that the large‐amplitude electric fields near the equatorial plane are consistent with SAPS by investigating the relationship between plasma sheet ion and electron boundaries, associated field‐aligned currents, and the spatial location of the electric fields. By incorporating high‐inclination DMSP data we demonstrate the spatial and temporal variability of the SAPS region, and we suggest that discrete, earthward propagating injections are driving the observed strong electric fields at low L shells in the equatorial magnetosphere. We also show the relationship between SAPS and plasmasphere erosion, as well as a possible correlation with flux enhancements for 100s keV electrons. Key Points: SAPS electric fields are shown in relation to equatorial magnetospheric particle boundaries RBSP and DMSP observations suggest that SAPS region is composed of numerous earthward propagating spatial structures SAPS electric fields are correlated with plasmasphere erosion